2008
DOI: 10.4314/ejhd.v22i1.10059
|View full text |Cite
|
Sign up to set email alerts
|

Quality of post-abortion care in public health facilities in Ethiopia

Abstract: Background: Comprehensive quality Post Abortion Care (PAC) is one of the important strategies to save lives where access to safe abortion is restricted by Law and services are inaccessible. Objective: The objective of the study was to assess the status of quality of PAC in health facilities of Amhara and Oromiya regional states. Methods: The study was cross-sectional by design and was conducted from November 2002 to March 2003. Patient interview, provider interview and direct service delivery observation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 3 publications
(3 reference statements)
2
19
1
Order By: Relevance
“…Meanwhile, most of them except one provider did not wear goggles and protecting boots. This finding goes in agreement with studies conducted in other part of the country [14]. This could be due to negligence and partially due to lack of some facilities like water and functioning sink.…”
Section: Variablessupporting
confidence: 92%
See 3 more Smart Citations
“…Meanwhile, most of them except one provider did not wear goggles and protecting boots. This finding goes in agreement with studies conducted in other part of the country [14]. This could be due to negligence and partially due to lack of some facilities like water and functioning sink.…”
Section: Variablessupporting
confidence: 92%
“…It is encouraging that the current study finding showed that range for waiting time to get the actual treatment was found to be 1 hour to one full day where as findings in other studies showed that the waiting time to be 1-7 days [15]. However, it is disheartening that finding of this study indicated that client satisfaction on PAC service delivery was lower as compared to previous studies done in the country where the majority (79.6% ) expressed their satisfaction with the services they received [14].…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Problems related to abortion were neglected and access to quality post-abortion care was very limited (4,5,6,7). Complications resulting from unsafe abortion are major public health problem in the country which affects all women in reproductive age.…”
Section: Introductionmentioning
confidence: 99%